Pharmacological treatment of presbyopia: A systematic review - Negin Haghpanah; Raid Alany (PAGEPress Publications, 2022)
The aim of this study was to identify the efficacy of drug agents for pharmacological Treatment of Presbyopia. Published research papers were reviewed using the relevant terms in PubMed, Science direct, Google scholar, Medline, Google patent, Ovid, Cochrane Database of Systematic Reviews, Scopus. In the initial search, 2270 records were obtained. By removing duplicate articles and all articles that did not meet the inclusion criteria or were inappropriate due to indirect relevance to the subject, 44 studies were selected. It should be noted that all studies had inclusion criteria. There are a number of topical pharmacological agents available for treating presbyopia such as FOV Tears and PresbiDrop. They consist of parasympathetic agent and non-steroidal anti-inflammatory drugs (NSAIDs), to contract the ciliary and pupil muscle and restore the accommodation. Another example of topical pharmacological agent is EV06. It is a lens-softening eye drop which can affect the rigid lens in presbyopia. Currently there is no pharmacological agent available to treat presbyopia. Although there are limited number of peer-reviewed articles available, the outcome for future agents under investigation are promising.